Face Veil and Lawo-Lambu: Negotiating Religious Practices Among Muslims and Catholics in Ende City - Yosep Aurelius Woi Bule; Adison Adrianus Sihombing (Al-Albab, 2022)
ABSTRACTThe phenomenon of wearing a face veil in Ende City has received a rather negative response from Catholics. The Catholics think that the face veil worn by Muslim women has created a social and emotional distance that disrupts the kinship system of Muslims and Catholics of the same ethnic culture. This study explores and analyzes the motivation for Muslims wearing the face veil, the reasons behind the response of Muslims and Catholics, and the negotiation efforts made by Muslims in responding to and accommodating the local culture of dressing among the Ende people. This study is qualitative research through in-depth interviews with Muslim and Catholic sources as well participant observations. This field study was conducted from July 2019 to December 2021. The data analysis process used was descriptive and interpretive. The findings of this study show that; first, the choice to wear the face veil comes from personal motivation towards piety of the faith of Muslim women. A face veil is not an expression of a suspicious radical movement and will not disrupt the kinship system as perceived by the Catholics. Second, it turns out that the response of the Catholics is due to the assumption that Muslim women who wear the face veil have left the local dress culture because they are adopting Arab culture and causing social rifts in daily life even though they are ethnically still brothers and sisters. Third, Ende Muslims combine the face veil with local clothing, the lawo-lambu, on different occasions. This combination is a negotiation process between personal autonomy towards a true Muslimah and a strategy to accommodate the beauty of the local dress, the lawo-lambu, so as not to lose their identity as Ende people who are predominantly Catholics.